Aspectos de la enseñabilidad de las ciencias sociales y humanas. (2021)
In the following lines I do an analysis about this pedagogic component in the field of the human and social sciences, beginning from some considerations about aspects that belong to them, in a way that we can establish how to understand “enseñabilidad” in higher education, starting from the areas where its knowledge is created, taking into account not only the investigator of its principles, processes and characteristics but also the teacher in his quality of mediator, researcher and communicator of the knowledge, who in his communicative action reproduces them whit its relevance, making them socially legitimate, and making possible the confrontation of theories and practices; and to the student who will study the theories in the epistemological, methodological, and didactical relation that is established in he process of learning necessary to develop the basic competences that the should have as a subject that is immerse in human and social spaces.